„Poetyckie Dyptyki” w poezji ks. Janusza St. Pasierba - Peroń, Małgorzata (Colloquia Litteraria, 2014)
‘Poetic diptychs’ in Fr. Janusz St. Pasierb’s poetry ‘Poetic diptychs’ distinguish themselves from a group o Fr. Janusz St. Pasierb’s poems inspired by the art of painting. These dual poems refer to the same branches of art (painting, sculpture, architecture) as a general rule. The dual sequences are put in the volumes next to each other. Apart from the subject matter they are linked by similar characteristics and nearly identical formulation of their titles. References to art are a pretext to ponder upon in a theological, existential and metapoetic manner. Dual nature of the voice points to multiple ways in which the visible can be interpreted. It also shows the necessity of precise defining of any meanings and presents the scope of difficulties related to inexpressibility.